Uprooting corruption and harnessing ethical leadership in Zimbabwe - Kanyane, M. H.; Mutema, Edson P. (Reach Publishers, 2021)
This chapter is subdivided into two sections: the conceptual and theoretical frameworks. The first section of the chapter conceptualises ethics, ethics architecture and its primary components from a local government perspective. The theories of ethics, for example, the teleological, deontological theories and theory of virtue ethics, are discussed in the second part of the chapter. Ethical theories assist in handling ethical issues in organisations.